Evaluation of Antioxidant Activity of Asystasia Travancorica Bedd (Acanthaceae) - V.R, Mohan; K, Paulpriya; P., Tresina Soris (Asian Journal of Biological and Life Sciences, 2016)
In vitro antioxidant activity of petroleum ether, benzene, ethyl acetate, methanol and ethanol extracts of Asystasia travancorica (Acanthaceae) was evaluated by studying 1, 1-diphenyl – 2- picrylhydrazyl (DPPH) radical scavenging activity, hydroxyl radical scavenging activity, superoxide radical scavenging activity, ABTs radical cation scavenging activity and reducing power using standard procedure. Total phenolic content was estimated by Folin –ciocalteau method. Flavonoid was determined by Aluminium chloride method. The total phenolics and flavonoids in methanol extract were found to be 0.54g100g-1 and 0.62g100g-1 respectively. Ethanol extract of A.travancorica is found to possess higher DPPH radical scavenging activity and reducing ability. Methanol extract of A.travancorica exhibited highest superoxide and ABTs radical cation scavenging activity. Petroleum ether extract of A.travancorica showed the highest hydroxyl radical scavenging activity. This study indicates significant free radical scavenging potential of A.travancorica whole plant which can be exploited for the treatment of various free radical mediated ailments.
Keywords: Asystasia; Methanol; Radical scavenging; Total flavonoids